Community based Adoption of Intercropping in Coconut Based Farming Systems of Kerala with special reference to Tuber Crops - Santhakumari, Kalavathi; V, Krishnakumar; RJ, Thomas; Thomas, George V; P, Anithakumari (JOURNAL OF ROOT CROPS, 2015)
Tuber crops are highly suitable for intercropping in coconut gardens at all growth stages. Hence these crops were included as the major intercrops for enhancing the livelihood security of coconut farmers under two projects funded by International Fund for Agricultural Development (IFAD)/The Coconut Genetic Resources Network (COGENT) and National Bank for Agriculture and Rural Development (NABARD) operated through Community Based Organizations (CBOs) under the aegis of Central Plantation Crops Research Institute (CPCRI). The projects were implemented in four coconut communities,Thekkekkara (under NABARD), Pathiyoor, and Devikulangara of Alappuzha District and Thodiyoor of Kollam District of Kerala (IFAD). Data related to area under intercrops, extent of adoption, income derived from the intercrops and the utilization pattern were recorded before and after the project using a standardized questionnaire template during 2005-2012 period. Data collection was done through personal interview with 609 CBO members and the data were coded and analysed using SPSS. All the four coconut communities indicated significant increase in the area and percentage of holdings under tuber crops and income from tuber crops alone as well as other short duration intercrops in general over the project period. The overall data for all the four communities revealed 3.7 fold increase in area under tuber crops alone and 29% increase in the holdings under adoption of tuber crops, whereas it was 2.2 fold and 24% in the case of intercrops in general. The share of income from tuber crops to total intercrop income increased from 49 to 60% in Thekkekkara, while that of the other three communities in general remained the same (72%) over the project period. The pre and post utilization pattern in terms of the value of product revealed increase in all categories- sold, consumed, supplied in kind and seed material- for tubers alone and intercrops together in all the four communities. In general, the area, production as well as income from tuber crops showed significant improvements through community based adoption. The proportion of tuber crops consumed was much higher (more than 60% of the total production) in Thekkekkara, while more than 50% of the total production was sold in the other areas. The results thus highlight the scope of intensifying the cultivation of tuber crops as food and cash crops to enhance the livelihood security of the coconut farmers.